2001
DOI: 10.1063/1.1385341
|View full text |Cite
|
Sign up to set email alerts
|

Metal-insulator-vacuum type electron emission from N-containing chemical vapor deposited diamond

Abstract: This letter presents a clear explanation of the electron emission mechanism of the high-resistivity N-doped diamond cathode. Due to the very low barrier to emission of electrons from the N-doped diamond conduction band into vacuum, electrons in the conduction band of diamond can establish an appreciable leakage current at very low anode voltage. When such a current starts to flow, there is a field which is developed across the diamond bulk. This field is observed as an increase in the electric field at the bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…[1][2][3][4][5][6][7] The discovery of negative electron affinity 8 ͑NEA͒ and the development of the chemical vapor deposition ͑CVD͒ technique 9 accelerated research in the field. However, the emission mechanism has not been clearly defined, largely due to the difficulty in determining the origin of emitted electrons.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The discovery of negative electron affinity 8 ͑NEA͒ and the development of the chemical vapor deposition ͑CVD͒ technique 9 accelerated research in the field. However, the emission mechanism has not been clearly defined, largely due to the difficulty in determining the origin of emitted electrons.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that most of the applied voltages drop in vacuum, as observed in the case of B-doped diamond[2]. Obtained V-d characteristics have different feature from heavily N-doped diamond with urea[3]. The slopes of all plots are almost straight when anode-cathode distances are over 0 m. The slope…”
mentioning
confidence: 69%
“…In this study, an a-Se based photodetector is fabricated using nitrogen (N) doped diamond cold cathode as signal read-out. With a negative electron affmity surface and M-I-V type emission [3], N-doped diamond emitter should provide sufficient emission current for wide dynamic range, as well as small dispersion angle for high spatial resolution. Furthermore, high-sensitivity photo detection has been demonstrated using carrier multiplication in a-Se [4].…”
Section: Introductionmentioning
confidence: 99%